Controle de uma formação VTNT-VANT baseado em espaço nulo - Moreira, Mauro Sergio Mafra (2020)
This work proposes a controller to autonomously guide a formation of two mobile robots, a differential drive wheeled one and an aerial one, in tasks of positioning. The controller is designed considering the paradigm of virtual structure, in which the vir